2015
DOI: 10.1111/1471-0528.13342
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of endometrial thickness for the detection of endometrial cancer in postmenopausal bleeding: a retrospective cohort study

Abstract: Objective To estimate the accuracy of transvaginal ultrasound (TVS) measurement of endometrial thickness (ET) in diagnosing endometrial cancer in postmenopausal women with vaginal bleeding (PMB).Design Retrospective cohort study.Setting One-stop PMB clinic in a Hong Kong teaching hospital. Main outcome measures Accuracy data for TVS ET presented as sensitivity, specificity, and area under the receiver operator characteristic (ROC) curve.Results Endometrial cancer was diagnosed in 3.8% of women. The median ET i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 32 publications
2
51
1
4
Order By: Relevance
“…We agree fully with the comment that in women with postmenopausal bleeding (PMB) a thick endometrium should be further evaluated to rule out malignancy. Thin endometrium rules out endometrial cancer . Measurement of endometrial thickness should therefore be the first step in the diagnostic work‐up of women with PMB.…”
mentioning
confidence: 99%
“…We agree fully with the comment that in women with postmenopausal bleeding (PMB) a thick endometrium should be further evaluated to rule out malignancy. Thin endometrium rules out endometrial cancer . Measurement of endometrial thickness should therefore be the first step in the diagnostic work‐up of women with PMB.…”
mentioning
confidence: 99%
“…Endometrial and cervical polyps were more prevalent and endometrial cancer was relatively rare. Although requiring further studies, a report from Hong Kong (3) showed that the prevalence of endometrial cancer among women with PMB in Hong Kong was 3.8%, which is much lower than the previously reported 10% in developed countries (17). This is one representative example which depicts the possibility that endometrial cancer prevalence rate may be quite different in the Asian population.…”
Section: Discussionmentioning
confidence: 68%
“…It is important to evaluate the cause of PMB because of its association with gynecologic malignancies (23456). Early diagnosis may help improve survival rates, hence several diagnostic tools such as transvaginal ultrasonography or hysteroscopy have been implemented for early and accurate detection of malignancy (1478910).…”
Section: Introductionmentioning
confidence: 99%
“…Transvaginal sonography is a widely accepted method of endometrial evaluation and many authors believe that normal sonography endometrial imaging sufficiently establishes absence of pathology in perimenopausal patients with abnormal uterine bleeding [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In the group of 105 patients sonohysteroscopy failed to detect endometrial polyps in 30 cases [18], SIS may also lead to erroneous diagnosis of blood clots as endometrial polyps [20]. Many authors do not regard sonohysterography results as sufficient evidence to confirm or exclude endometrial abnormalities [4,6,12,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%